2019
DOI: 10.1016/j.jsps.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility study of rosmarinic acid with excipients used in pharmaceutical solid dosage forms using thermal and non-thermal techniques

Abstract: Rosmarinic acid (RA) is a phenolic compound that presents well-documented anti-inflammatory, antioxidant and antitumor activities, and based on its pharmacological potential and poor bioavailability, several solid dosage forms have been developed to RA delivery. Therefore, in literature, there are no reports about RA compatibility with excipients. In this regard, the aim of the present study was to evaluate, for the first time, the compatibility of RA with excipients commonly used in solid dosage forms at a 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
3
17
0
1
Order By: Relevance
“…The excipients used in the formulation were chosen by the pre-formulation assays in the DSC and FTIR-ATR studies. Of the four excipients, only lactose monohydrate showed a possible interaction with the extract (Figure 2); the lactose curve demonstrated three endothermic events related to dehydration (146.82 • C), melting (218.99 • C) and thermal decomposition (240.86 • C), respectively, which were identical to the results obtained by Pereira et al [30] and may suggest chemical incompatibility [31].…”
Section: Discussionsupporting
confidence: 83%
“…The excipients used in the formulation were chosen by the pre-formulation assays in the DSC and FTIR-ATR studies. Of the four excipients, only lactose monohydrate showed a possible interaction with the extract (Figure 2); the lactose curve demonstrated three endothermic events related to dehydration (146.82 • C), melting (218.99 • C) and thermal decomposition (240.86 • C), respectively, which were identical to the results obtained by Pereira et al [30] and may suggest chemical incompatibility [31].…”
Section: Discussionsupporting
confidence: 83%
“…RA is an ester of caffeic acid and 3,4-dihydroxyphenyllactic acid that can be widely found in many plants, especially rosemary, perilla, basil, and mint [ 48 ]. RA possesses remarkable pharmacological activities, such as antioxidant and anti-inflammation properties, and with regard to neurodegeneration, cancer, diabetes, and bone diseases [ 48 , 49 , 50 ]. Our studies analyzed the RA level of each PSM fraction, with results showing that the SMEF contained the highest amount of RA, followed by SME, SMWF, SMHF, and SMDF, as shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant activity as IC50 and ferric reducing/antioxidant power (FRAP) of perilla seed meal (PSM) fractions determined by different assays using ascorbic acid and rosmarinic acid (RA) as the positive control. ABTS, 2,2-azino-bis-3ethylbenzthiazoline-6-sulfonic acid; SMEF, seed-meal ethyl acetate fraction.…”
mentioning
confidence: 99%
“…RA is a water-soluble polyphenolic phytochemical with free-radical scavenging and antioxidant effects (Veras et al, 2019). Al-Alami et al (2017) showed that RA had a reversal effect on metronidazole-induced infertility in male albino rats.…”
Section: Discussionmentioning
confidence: 99%
“…RA is a water‐soluble polyphenolic phytochemical with free‐radical scavenging and antioxidant effects (Veras et al., 2019). Al‐Alami et al.…”
Section: Discussionmentioning
confidence: 99%